PROFILE OF WOMEN ATTENDED BY A POLE OF THE ACADEMIA DA SAÚDE PROGRAM IN SOBRAL, CEARÁ, BRAZIL - Joel de Almeida Siqueira Junior; Francisco Timbó de Paiva Neto; Antônio Cleilson Nobre Bandeira; Kalil Janvion Bezerra Silva; Cassiano Ricardo Rech (Journal of Physical Education)
ABSTRACT The aim of this study was to describe the characteristics of women attended in the pole of the Academia da Saúde Program in Sobral, Ceará. A descriptive, cross-sectional study was carried out with 102 program participants. The information was obtained through the application of an integrated body assessment form. The following variables were collected: age, skin color, marital status, occupational status, body mass index, use of medicines, alcohol and tobacco use, morbidities and body self-perception through a valid scale. Descriptive statistics (mean, standard deviation, absolute and relative frequency) were used for data analysis. The results show that the profile of users who visit are middle-aged women (47.1%), white (56.9%), who live with their partners (66.7%), have some self-reported morbidity (67.6%), unemployed (37.2%) and with negative body self-perception (60.8%). The actions developed at the PAS of Sobral have ensured greater participation of middle-aged, white women, who live with a partner, have some self-reported morbidity, are mostly unemployed and have negative body self-perception. In addition, the actions have included a negligible participation of men. This study guides the actions of the PAS hubs to be monitored and evaluated so that managers can understand how the proposed activities reverberate in relation to the users' profile, also enabling the comparability between different hubs of the program, favoring the development of strategies that present user adherence proposed activities.